PENYULUHAN TENTANG HIV DAN AIDS DI WILAYAH KERJA PUSKESMAS BERINGIN JAYA KUANTAN SINGINGI - R. Sri Ayu Indrapuri; Danil Hulmansyah; Sherly Mutiara (Awal Bros Journal of Community Development, 2020)
HIV and AIDS are dangerous diseases which cannot be cured. Based on data from the Riau Province Health Office from January to September 2012, it shows that the number of HIV and AIDS cases in Riau reached 946 people and 580 were tested positive for HIV. This makes the author interested in conducting counseling about HIV and AIDS in the working area of ​​the Beringin Jaya Community Health Center, Kuantan Singingi Regency. This inquiry aims to find out whether the public knows about HIV and AIDS, then to find out whether the public already knows about the transmission of HIV and AIDS and to find out whether the public knows about the prevention of HIV and AIDS. The method used is counseling with the delivery of information through lectures as well as sharing and conducting questions and answers to the public to increase understanding and awareness of HIV and AIDS. This counseling was held on August 6, 2019 at 08.00 WIB to 16.00 WIB in the working area of ​​the Beringin Jaya Health Center, Kuantan Singingi Regency. The result of this counseling was the implementation of counseling about HIV and AIDS in the community in the working area of ​​the Beringin Jaya Community Health Center, Kuantan Singingi Regency by providing information and understanding to the community about the importance of a healthy lifestyle to prevent people from contracting HIV and AIDS.